Adult-onset Langerhans cell histiocytosis with multisystem involvement: A rare case report - Yaman M․ Alahmad; Omar Al Mukdad; Ahmad Huneity; Sarah Sayed; Renan Adam; Alaa Al-Taie (Radiology Case Reports)
Langerhans cell histiocytosis (LCH) is a rare disorder, especially among adults, characterized by abnormal accumulation of dendritic histiocytes in various tissues, presenting as either single- or multi-system disease. In adults, spinal involvement is less common than long bone, while central nervous system manifestations, such as pituitary gland enlargement and stalk thickening, affect about a quarter of adult patients and may lead to significant endocrine disorders. Salivary gland involvement is another extremely rare manifestation of LCH. We report a 46-year-old lady who presented with back pain along with sensory and motor deficits in the lower limbs. Her blood pressure was elevated. Computed tomography angiography spotted a T6 vertebral body compression fracture. Magnetic resonance of the spine showed T6 vertebral body pathological collapse with epidural soft tissue component compressing the spinal cord. Other imaging modalities showed features suggestive of central nervous system and salivary gland involvement. She underwent T4-T8 pedicle screws fixation with T6 decompressive laminectomy and biopsy of the epidural lesion, which revealed histopathological features of LCH. This is an extremely rare case of adult-onset LCH with multi-system involvement: musculoskeletal, salivary and central nervous systems. This case could serve as a crucial reference for both clinicians, radiologists and researchers, enriching the existing knowledge base on adult-onset LCH.